The impact of digitalization on future leaders skills - Senka Borovac Zekan; Agata Borowska Pietrzak; Marina Palada (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Introduction: Digitization has revolutionized various aspects of business and society, presenting new challenges and opportunities for leaders in the digital era. This paper examines the impact of digitization on leadership traits and skills and identifies the most significant changes that have occurred in the face of new societal challenges. Methodology: A literature review and a survey were conducted to determine the qualities and skills of future leaders in the digital age. The study focused on the most evident changes caused by digitization, such as knowledge sharing, innovation, cooperation, networking, and communication. Results: The study finds that future leaders must possess adaptability, vision, empowerment, collaboration, digital literacy, data-driven decision-making, agile thinking, design thinking, ethical awareness, and emotional intelligence. The findings suggest that future leaders must adapt to the changes brought by digitization and incorporate new skills and traits to be effective in the digital world. Discussion: Leadership theories of the past no longer fully reflect the skills and abilities that leaders require in the modern age. The digital age has brought a new approach to leadership, and digitization has significantly shaped this new image. To be an effective leader today, one must embrace digitization and continuously develop new skills to stay ahead of the curve. The following has increased the need for continuous skills improvement through formal and informal education. Conclusion: The research showed that digitization has a significant impact on knowledge sharing, innovation, collaboration, networking, and communication. It has a minor effect on trust and efficiency. Leaders of the 21st century should adapt to continuous changes and involve all employees in decision-making and task execution to optimize their performance.